Case report: A pediatric case of repeated false-positive urea breath test for Helicobacter pylori without decreased gastric acid secretion - Nishino, Masafumi; Kakiuchi, Toshihiko; Fukuda, Kayoko; Yoshiura, Masato (Frontiers in Medicine, 2023)
The urea breath test (UBT) is often used to diagnose Helicobacter pylori infection and for its eradication. However, this text can give positive results even for other urease-active bacteria other than H. pylori. Even after the successful eradication of H. pylori, the presence of other urease-active bacteria in the gut and oral cavity can lead to positive UBT results in patients with decreased gastric acid secretion. Herein, a 15-year-old boy was diagnosed with H. pylori infection through the testing and treatment program for H. pylori for third-year junior high-school students in Saga Prefecture initiated in 2016. He underwent triple therapy comprising vonoprazan; however, UBT was found to be positive even after therapy. The results remained positive even after fourth-line eradication therapy. Stool antigen, PCR using gastric fluid, microscopy, culture, and rapid urease tests were all negative. Pepsinogen levels were normal, and none of the findings suggested autoimmune gastritis. Gastric microflora analysis revealed oral flora showing urease activity. UBT is considered useful for determining the successful eradication of H. pylori; however, it may give false-positive results for both H. pylori infection and eradication judgment. Although the patient did not have autoimmune gastritis or decreased gastric acid secretion, it is presumed that oral commensal bacteria showing urease activity inhabited the stomach, resulting in the persistently positive UBT results. In conclusion, repeated false-positive UBT results for H. pylori may occur even without gastric acid hyposecretion. If H. pylori eradication is unsuccessful based on UBT, additional test by stool H. pylori antigen tests should be considered.